On symbol correspondences for spin and quark systems - Alcântara, Pedro Antonio Soares de (2022)
In this work, we investigate the correspondence principle applied to mechanical systems symmetric under a compact Lie group by means of symbol correspondences. In the first part, we consider systems symmetric under SU(2), the so-called spin systems: we verify conditions under which symbol correspondences present localization of pure states at the semiclassical limit, which provides a new criterion for the emergence of classical dynamics; then, we introduce the notion of sequential quantization from which we get a new characterization of asymptotic localization. In the second part, we begin the study of symbol correspondences for systems symmetric under SU(3), the quark systems: we characterize the symbol correspondences for such systems and obtain some properties and formulas for twisted products induced on the spaces of symbols.